Consumer knowledge, attitudes, and behaviour regarding food safety – A perspective from Laos - Gyula Kasza; Tekla Izsó; Atilla Kunszabó; Dávid Szakos; István Lénárt; Emese Bozánné Békefi; Khamphouth Vongxay; József Popp; Judit Oláh; Zoltán Lakner; Widya Satya Nugraha; Lajos Bognár; et al. (Heliyon, 2024)
Primary research data on food chain safety at consumer level is needed to help policymakers to decrease the risk of foodborne infections in the Lao People's Democratic Republic. Therefore, the objectives of this study are to 1) determine Lao people's food safety knowledge, attitudes, and intentions and identify the most influential factors that shape their food safety behaviour, and 2) to support the government in the development of more efficient risk communication programmes. A paper-based consumer survey was implemented to collect quantitative data on the selected topics about Laotian consumers, as well as on the equipment of households regarding the conditions and tools necessary for safe food preparation and storage. A model was developed based on the extended Theory of Planned Behaviour (TPB), and partial least squares structural equation modelling (PLS-SEM) was applied to analyse the factors that affect food safety behaviour. The elements of Knowledge and Perceived Behavioural Control positively influence behaviours, such as using separate chopping boards for raw and ready-to-eat foods. According to the model, only 10 % of the Intentions would be translated into Behaviours, which gap can be explained by the lack of a hygienic environment. Although the survey indicated that Laotian people intend to follow food safety guidelines, participants felt they lacked sufficient knowledge. This perception was validated by the knowledge test and behavioural part of the study. In the light of these findings, it is essential to raise awareness and promote food safety knowledge and interventions, such as enhancing food safety education in childhood. This would help to facilitate and encourage adopting safe practices to improve overall food safety at the consumer level, delivering positive impacts also to the food business sector.